1981
DOI: 10.1063/1.442497
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of nonadiabatic reactions. I. F (2P3/2, 2P1/2)+HBr (DBr)→HF (DF)+Br (2P3/2, 2P1/2)

Abstract: A crossed molecular beam study has been performed on the nonadiabatic reactions F(2P3/2) [F(2P1/2)]+HBr(DBr)→HF(DF)+Br(2P3/2) [Br(2P1/2)]. Atomic F came from a seeded supersonic jet, so that the cross sections Sr(Br) and Sr(Br) could be measured as a function of collision energy ET = 1–11 kcal/mol. The reagent ratio [F]/[F] was varied by means of a variable temperature F atom source. Products Br and Br were detected by tunable vacuum ultraviolet laser-induced fluorescence (VUV LIF). The reaction cross sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…v c is the relative velocity of the reactants in the laboratory frame. 14b,c, 20 The decrease of the Br number density caused by scattering out of the detection region is taken into account by involving the Br speed, v Br , in the laboratory frame in the above equation. In the data analysis, the speed and angular distributions of the Br-atoms were assumed to be independent of OH orientation because of the lack of information about the product velocity distribution in our experimental setup.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…v c is the relative velocity of the reactants in the laboratory frame. 14b,c, 20 The decrease of the Br number density caused by scattering out of the detection region is taken into account by involving the Br speed, v Br , in the laboratory frame in the above equation. In the data analysis, the speed and angular distributions of the Br-atoms were assumed to be independent of OH orientation because of the lack of information about the product velocity distribution in our experimental setup.…”
Section: Resultsmentioning
confidence: 99%
“…Such a high voltage provides enough electric field strength (B8.5 kV cm À1 ) in the collision region in order to attain the high field limit for complete orientation of the OH (X 2 P) f states. 20 Besides, a guiding field was applied to synchronize with the orienting field in order to bridge the gap between the hexapole and the orienting field. Note that without state selection, HBr molecules remain randomly orientated in the presence of an 8.5 kV cm À1 orienting electric field.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth emphasizing that in three-atom reactions of the heavy-light-heavy type (H þ LH) such as F þ HBr and Cl þ HCl, for which the PES is skewed, the reaction cross-section may decrease in terms of the collision energy. [14][15][16] Though the present process involves four atoms, it may be viewed as a H þ LH reaction where L is still a hydrogen atom while the H atoms are, respectively, Br and the OH radical. If this view is correct, one is not really surprised to observe experimentally that the reaction cross section decreases with increasing collision energies.…”
Section: Resultsmentioning
confidence: 99%
“…We note, however, that in an earlier study of the F + HBr -FH + Br reaction Hepburn et al found that only a small fraction (B1/20) of the Br products were in the spin-orbit excited state. 49 Finally, there is also the possibility that the adiabatic PES is not sufficiently accurate, as discussed below.…”
Section: Iiic Vibrational State Distributionsmentioning
confidence: 99%